X-Ray Description: Past, Present, Future (Texas Journal of Medical Science, 2024)
The wide variety of description protocol styles that currently exist in radiology diagnostics is proof that a basic, universal description format has not been found, and there is no uniform standard for describing studies. All this allows us to formulate the main goals and objectives that must be overcome to improve and create a new form of radiological description protocols - protocols of the future.